Morbihan disease: a therapeutic challenge - Fernanda Cabral; Lara Caroline Lubbe; Monisa Martins Nóbrega; Daniel Lago Obadia; Roberto Souto; Alexandre Carlos Gripp (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Morbihan disease is a rare condition characterized by chronic and persistent erythematous solid edema localized on the face. It is believed to be a complication of rosacea and may occur at any stage of the disease. Features of this condition include variable therapeutic response and great refractoriness. We report a case of a 61-year-old man with rosacea history diagnosed with Morbihan disease, who showed excellent therapeutic response with the combination of deflazacort and oral isotretinoin but developed recurrence after corticosteroid discontinuation. We believe that in severe cases of lymphedema of the face this combination is effective and corticosteroid suspension should be done slowly and gradually.